Assay of Physicochemical and Statistical Analysis of Textile Dyeing Effluent Generated from Different Fabrics - Muhammad Owais Chughtai; Asad A Zaidi; Abdul Hameed Memon; Ahmad Hussain; Arsalan Ahmed (Journal of Sustainable Environment)
Textile Industries play a significant and central role globally for the economic prosperity of numerous countries. Due to varied methods of dyeing processes involving enormous amount of water the textile processing units are blamable for major environmental pollution issues worldwide as this wastewater is released without appropriate treatment in nearby water channels. This research is aimed to conduct the physicochemical and statistical analysis of the effluent generated from dying of different fabrics. The parameters such as Power of Hydrogen Ion Concentration (pH), Conductivity, Total Dissolve solid (TDS), Total Suspended Solid (TSS), Total Hardness (TH), Biological Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Chloride (Cl-1), Sulphate (SO4-2), Sodium Ion (Na+1), Magnesium Ion (Mg+2) and Calcium Ion (Ca+2) were analyzed. The outcomes of the analysis were correlated with the National Environmental Quality Standard (NEQS) of Pakistan and World Health Organization (WHO). It was found that all the parameters were within permissible limits except pH, TH and Ca+2. The superfluous concentration of the pollutants indicates that the effluent is polluted with respect to about mentioned parameters. Such practices are creating hazardous effects on the ecology of terrestrial and aquatic life and pose a threat to the local environment.